PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS VA SD NEGERI 034 TARAIBANGUN - Yuni viani; Hendri Marhadi; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: this research do it because study result of social science from students SDN 034 Taraibangun grades VA very bad. The KKM in the school about 70. There are 35 students in the class but just 8 students (22,86%) reach the point of KKM. while 27 student (77,14%) not reach get it. With class scores 59,37. The purpose from research is to increase result and process social science learning at students of SDN 034 Taraibangun grades VA in using cooperative learning model of course review horay. The result of this research get average base score about 58,37 increase about 19,19% to be 69,57. At cycle 2 average student score have increase too about 42,44% to be 83,14. At the complete clasical base score of social science mayor about 22,86% (not passed). After used tipe of cooperative model of course review horay in cycle 1 get increase result in complite clasical score about 62,86% (still not passed) and in cycle 2 get increase result of complite clasical score about 88,57% (passed). The teacher activity in 1st metting in cycle 1 in percentage about 63% with bad category, 2nd metting increase to be 75% with good category. The student activity ties 1st metiing in cycle 1 have 63% with bad category, and 2nd metting increase to be 71% with enough category. The student activity 1st metting in cycle 2 have 79% with good category, 2nd metting increase to be 88% with very good category.Key Words: Course Review Horay, Learning Result of Social Science